Effect of Nigella sativa supplementation on human lipids: Systematic review - Al-Naggar R.A.; Osman M.T.; Mohamed I.N.; Abdulghani M.A.; Khairun Nain Nor Aripin (Open Science Publishers LLP Inc., 2024)
Indexed by SCOPUS